Applications of structural equation modelling - Chin, Chi Loong (Nanyang Technological University, 2021)
Structural Equation Model (SEM), which is a set of multivariate statistical methods, is applied in modelling the relationships between the latent variables Transport Infrastructure, Economic Growth, and Environmental Quality in two datasets. This paper starts with the introduction of the statistical technique and previous works on modelling the aforementioned three variables. Next, descriptions of the data collected will be elaborated and final results are presented in the last part. The results coincide with what we hypothesized beforehand, thus proving the correlation of the three variables.